Professional Competence of Business and Tourism Vocational School Teachers: The Effectiveness of Online Training and the Success of Industrial Internships with Achievement Motivation Mediation - Rifky Kurniawan; Amrozi Khamidi; Karwanto Karwanto; Mochamad Nursalim; Syunu Trihantoyo; Mohammad Syahidul Haq (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the direct and indirect influence of the effectiveness of online training, the success of industrial internships, the motivation for achievement and the professional competence of vocational school teachers in the field of business and tourism. This study uses a quantitative approach with a constellation model. The sample in this study was 161 teachers using the proportionate stratified random sampling technique. The data collection technique is in the form of a questionnaire using the Likert scale. The test of the requirements of the research analysis used the normality test, the linearity test, the multicollinearity test and the heterokedasticity test. The data analysis technique in this study uses path analysis. The results of the data analysis are as follows: 1) The effectiveness of online training has a direct effect on the professional competence of teachers by 0.159 (15.9%) with a t count of 2,282 1,975. 2) The success of industrial internships has a direct effect on the professional competence of teachers by 0.269 (26.9%) with a t count of 4.034 1.975. 3) Motivation for achievement has a direct effect on the teacher's professional competence of 0.489 (48.9%) with a t calculation of 7.370 1.975. 4) The effectiveness of online training had a direct effect on achievement motivation of 0.448 (44.8%) with a t count of 5.941 1.975. 5) The success of industrial internships has a direct effect on achievement motivation of 0.338 (33.8%) with a t count of 4.474 1.975. 6) The effectiveness of online training has an indirect effect on teachers' professional competence through achievement motivation of 0.2190 (21.90%) with a sobel test value of 4.62 1.96). 7) The success of industrial internships has an indirect effect on teachers' professional competence through achievement motivation of 0.1652 (16.52%) with a sobel test score of 3.84 1.96.